Management control decisions in gym services in Portugal and Brazil during pandemic confinement COVID-19: accounting information systems approach - Leite, Joaquim (2023)
The present research aimed to identify similarities and differences in management control decisions implemented in gyms in Portugal and Brazil in reaction to the pandemic confinement COVID-19. The theoretical approach was in the context of Information Systems (ISs). The cases of one gym in Portugal and one in Brazil were studied through a qualitative methodology using the holistic multiple case study method. Data collection was made through a content analysis and interviews with managers of both gyms. The results allow the conclusion that the global and sudden pandemic confinement COVID-19 affected management control decisions in gym services, especially the budget control which showed abnormally unfavorable deviations in income, expenses and investments. Although the studied gyms were located in different continents (Portugal and Brazil), the managers' control decisions were similar, evidencing an immediate damage containment response and short-term resilience. As for the ISs, the results showed that the instrumental usefulness of these systems implemented in both gyms was never questioned as a support to operation and decision making. But the temporary and drastic reduction in the activity of the gyms, in response to an unexpected confinement context, meant a consequent and natural reduction in their use. As for the extent of the theoretical framework, the study reinforces the weaknesses of the budgeting process in an unexpected pandemic context, on the one hand, and the interdependence between ISs and management control decisions in the gym services sector. Additionally, without questioning that interdependence relationship, it can also be interpreted that ISs have an instrumental character because they are more dependent on managers' decisions and critical junctures.